Journal of Medical Case Reports - Kidd, Michael
Journal of Medical Case Reports will consider any original case report that expands the field of general medical knowledge, and original research relating to case reports. Case reports should show one of the following: Unreported or unusual side effects or adverse interactions involving medications Unexpected or unusual presentations of a disease New associations or variations in disease processes Presentations, diagnoses and/or management of new and emerging diseases An unexpected association between diseases or symptoms An unexpected event in the course of observing or treating a patient Findings that shed new light on the possible pathogenesis of a disease or an adverse effect Suitable research articles include but are not limited to: N of 1 trials, meta-analyses of published case reports, research addressing the use of case reports and the prevalence or importance of case reporting in the medical literature and retrospective studies that include case-specific information (age, sex and ethnicity) for all patients.